IMPLEMENTATION OF PUBLIC SERVICES IN THE FIELD OF GOVERNANCE GOVERNMENT IN TANETE RILAU DISTRICT, BARRU REGENCY - Ikhsan Adiputra Lubis (Meraja journal, 2021)
Public services that are the focus of the study of the discipline of Public Administration Sciences in Indonesia, are still issues that need to be given comprehensive attention and completion. Basically every human need service, even in the extreme can be said that service can not be separated with human life. Kecamatan which is one of the extension of the central government in providing public services. Governance is one of the most public services the public has ever needed since he was born until he died. Therefore, the researcher is interested to discuss the Impelementasi Public Service in the Field of Governance in Tanete Rilau.In research conducted by researchers, researchers used descriptive method research method with a qualitative approach to collect data and information. Researchers will try to analyze the data obtained from various sources to answer the problems of Public Service Implementation in the Field of Governance in Barru District Tanete Rilau. Researchers use four techniques in analyzing the data that is, observation, interview, documentation and after that data from observation, interview and documentation will trianggulasi.Based on the results of the interviews that have been described in the previous chapter, where there are six (6) things are grouped by researchers to facilitate in understanding the results of interviews. And from the results of the interview ditrianggulasikan with the results of observation and documentation that exist, the researchers will try to analyze how actually Implementation of Public Service in the Field of Governance in the District of Tanete Rilau.